PENGARUH PEMBERIAN REWARD TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS 4 DI MIS AL-FATAH SINGKAWANG - Muhammad Sidik; Murdani, Eka; Suprapto, Wasis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to: (1). Determine whether there is an influence on the learning results of students between classes that apply reward and classes that do not apply reward (2). Determine the extent to which reward influences the learning results of Bahasa Indonesia class 4 at MIS AL-Fatah Singkawang. (3). Determine the extent to which the learning results of students increase after the implementation of reward on the learning results of Bahasa Indonesia class 4 at MIS AL-Fatah Singkawang.The experimental research design used in this study is Nonequivalent control Group Design. The population in this study is class 4A and class 4B at MIS Al-Fatah Singkawang.Based on the research results and discussion in the previous chapter, it can be concluded that: (1). There is an influence on the learning results of students between classes that apply reward and classes that do not apply reward. This is proven by the data analysis that was conducted using statistical parametric tests, namely the, which shows that the results of the post-test are significant. (2). Reward has a moderate effect on the learning results of Bahasa Indonesia class 4 at MIS AL-Fatah Singkawang. This is proven by the data calculation of students using the Effect Size formula, which obtained a value of Effect Size (Es) of 0.7, located in the moderate criteria. (3) The implementation of reward experiences a moderate increase in the learning results of cognitive domain students in the origin material class 4 at MIS AL-Fatah Singkawang.